CONTENT OF EMOTIONAL CATEGORY CULTURE OF PERSONALITY ”IN MODERN PEDAGOGICAL RESEARCH (Pedagogy of Higher and Secondary Education, 2022)
The author of the article considérés the essence of the category “emotional culture ”. A brief analysis of pedagogical writing in the given problem is adduced in the article.